Estratégia de vida do peixe anual Hypsolebias antenori (Cyprinodontiformes: Rivulidae) do semiárido brasileiro - Nascimento, Wallace Silva do (2014)
This work deals with the life strategy of an endangered annual fish, Hypsolebias antenori (Cyprinodontiformes: Rivulidae), of the Brazilian semiarid region. The eggs of these fish hatch at the onset of the rainy season, grows rapidly and they reproduce during the rainy season. When the water puddles dry out, the entire population dies. The resistant eggs which are buried in the bottom of the dried pools go through diapause stages, during which time the embryonic development becomes temporarily arrested. With the onset of the next rainy season, the eggs hatch and a new generation is formed. Specimens of H. antenori were captured during 2011 and 2013, in temporary water pools located in the hydrographic basin of river Jaguaribe in Ceará, Brazil. Sex ratio, the length-weight relationship, the growth type, first sexual maturity, anatomy and histology of the digestive tract, development of gonads, reproductive strategy, karyotypic pattern of the species, and the conservation status of H. antenori were investigated. The results of this study are presented in the form of eight articles. The first article is about the fish faunal composition of the hydrographic basins of Rio Grande do Norte, Brazil, wherein the record of H. antenori is included. The second article deals with the sex ratio, secondary sexual characteristics of males, the length-weight relationship and the type of growth. Males show a pattern of intense coloration with well developed fins. The sex ratio showed a significant predominance of females (1M:1.7 F). Males were larger in length and weight. The equation of weight and total length relationship was Wt=0.0271Lt3,8937, showing a positively allometric growth, indicating greater increase in weight than in length. The third article discusses the anatomy and histology of the digestive tract of H. antenori. It is considered as a generalist feeder with characteristics of omnivore, which utilizes different food sources. The fourth article discusses the stages and phases of gonad development and type of spawning of H. antenori. The fifth article is about the r reproductive strategy adopted by H. antenori which helps in successful reproduction over a short period of life. The sixth article deals karyotypic pattern of the species, constituting the first cytogenetic contribution to the genus. The seventh article discusses about the risk of extinction of this species which suffers a series of threats, such as, habitat loss through land use, deforestation, construction of reservoirs, pollution due to domestic and industrial sewage, besides pesticides and agrochemicals. Furthermore, decreasing rainfall and intensification of aridity due to global climate changes, interferes with the reproductive cycle. The eighth article deals with aggressive behavior adopted between males and among females during reproduction. All temporary water pools sampled during this study were in high degree of degradation, mainly due to human action. There is a great need for conservation measures to protect the populations of annual fish, including the creation of protected areas in the semiarid ephemeral aquatic environments of Brazil